SIMPLIFIED METHOD FOR PREDICTION OF SETTLEMENT IN BAMBOO PILES-REINFORCED PEAT UNDER EMBANKMENT - Maulana, Maulana; Hanova, Yudha; Waruwu, Aazokhi; Putra, Arya Ratama (Journal of Applied Engineering Science, 2019)
Analysis of settlement predicted is required to determine the appropriate time to perform additional loading and how big embankment load that can generate sufficient compression on peat soil. The settlement of peat was investigated by a program of embankment load testing. The model of tests were conducted in the laboratory to be used as a reference for etimated settlement at the certain time and load. The test result indicated that etimated settlement has the same pattern with the pattern of observations data. This simple method can be used to estimate how long and how much embankment load is applied on peat soil up to get a addition of relatively small settlement.
Keywords: bamboo; settlement; soils; peat; embankment